(untitled) (Swiss Medical Weekly, 2020)
INTRODUCTION Code status discussions are useful for understanding patients’ preferences in the case of a cardiac/pulmonary arrest. These discussions can also provide patients with a basis for informed decision-making regarding life-sustaining treatment. We conducted a survey to understand current practices and perceptions of code status discussions in a tertiary-care Swiss hospital. METHODS We performed systematic interviews across different departments of the University Hospital of Basel. We interviewed 258 physicians and 145 patients who were hospitalised between May and July 2018 using a questionnaire designed to assess the use of code status discussions and to gauge patients’ individual experiences and opinions. RESULTS A total of 61.4% of patients did not recall having had a code status discussion during the hospital stay. However, a higher proportion of medical patients compared to surgical patients recalled having had a discussion (43.6 vs 22.4%, p = 0.03). For 9 out of 38 (23.7%) patients who did recall the discussion, there was a lack of agreement between the preference given in the interview regarding resuscitation measures and the documented code status in the medical electronic chart. Furthermore, a majority of physicians (72.4%) recalled defining a do-not-resuscitate (DNR) status for a patient without prior discussion with the patient. Physicians who recalled determining the DNR status without patient consultation reported conflicts with patients and relatives regarding code status at a higher rate compared to physicians who did not define DNR status without consultation (62.4 vs 39.4%, p <0.001). CONCLUSION A majority of patients do not report having discussed code status during their hospital stay and physicians frequently omit such discussions, thereby potentially failing to attend to patients’ preferences for care. Physician training regarding code status discussions may improve the quality of informed decision-making and patient-centred care.